The isolation of a plasma-derived γγ' fibrinogen: Fibronectin mixture that forms a novel polymeric matrix. (December 2018) - Ismail, Ayman E.A.; Fabian, Frank M.; Wang, Ou; Lei, Yuguo; Carlson, Mark A.; Burgess, Wilson H.; Velander, William H.
Graphical abstract: Highlights: A γγ'FI:FN mixture can be isolated at the same ratio as in human plasma. The γγ'FI:FN mixture at 20–50 mg/ml does not cryoprecipitate at 4 °C. A solution of γγ'FI at 15–30 mg/ml cryoprecipitates at 4 °C. A strong fibrin formed (SEMS = 16 kDyne/cm 2 ) at only 9 mg/ml γγ'FI:FN. Cross-linked fibronectin aggregates periodically associate with γγ'FI fibrin. Abstract: Human plasma fibronectin (FN) enhances fibrin polymer strength and is typically present at <5% in fibrinogen (FI) surgical tissue sealants. We describe a purification process to obtain a mixture of γγ' fibrinogen (γγ'FI) and FN at about the same mass concentration levels as occurs in plasma. Ammonium sulfate precipitation and DEAE chromatography of solvent-detergent treated plasma cryoprecipitate selectively concentrated γγ'FI and FN while effectively removing the γγFI component from FI. An interaction between γγ'FI and FN was observed by High Pressure Size Exclusion Chromatography (HPSEC) and Dynamic Light Scattering (DLS). A strong fibrin matrix was formed from treatment by a mixture of recombinant thrombin (rFIIa) and recombinant factor XIII (rFXIII). The γγ'FI and FN fibrin had an asymptotic shear elastic modulus strength observed by thromboelastography (TEG) of 16 kDynes/cm 2 versus 9 kDynes/cm 2 obtained from γγFI and FN. Confocal microscopy showed that the γγ'FI:FN fibrin matrix had a novel structure: γγ'FI fibers were periodically wrapped with FN aggregates. These studies provide a method for making a strong plasma-derived fibrin matrix having only 9 mg/ml total protein of γγ'FI, FN when polymerized at high levels of rFIIa and rFXIII activity.